Translation and the Literary Text - Ponzio, Augusto (TTR, 2007)
AbstractIn the present paper we shall focus on literary translation, on the question ofthe translation of “complex” or “secondary” texts, but with the intention of makinga contribution to the problem of translating non-literary, “simple,” “primary” textsas well. In other words, we shall examine the problem of text translation from asemiotic perspective. In fact, this study founds translation theory in sign theorydeveloping a semiotic-linguistic approach to the problem of translation in thedirection of so-called interpretation semiotics which also implies the semiotics ofsignificance. Translation concerns both simple and complex texts, which correspondrespectively to Mikhail Bakhtin’s primary and secondary texts. Simple texts concernnon literary discourse genres whilst complex texts the literary genres, where theformer are better understood in the light of the latter, and not vice versa. Thispaper also focuses on the concept of the literary text as a hypertext maintainingthat the hypertext is a methodics for translative practice. The relation between thetext and language understood as a modeling device is also important for anadequate theory of translation and sheds light on the question of translatability.Another central issue in this study is the relation between translation andintertextuality.